PERLINDUNGAN HUKUM TERHADAP PERDAGANGAN ANAK DENGAN MODUS PERNIKAHAN DALAM PERSPEKTIF VIKTIMOLOGIS - Islamia Ayu Anindia (Fakultas Hukum Universitas Pasundan, 2018)
Along with the development of the age, evil also develops in each era, as will the mode of crime, one of which is the crime of child trafficking. The new mode that emerged was marriage. In this crime, even though it is wrapped in a marriage, basically here the child will be a victim, because it will have physical, psychological, and spiritual effects that can last a lifetime which can then threaten the child's life. The form of protection that can be given to victims is by providing access to justice and fair treatment, providing restitution, compensation and assistance in terms of legal, material and non-material assistance, as well as assisting victims by giving strict and severe sanctions to child traffickers who commit child trafficking with marriage mode. Keyword: Trafficking, Child Marriage.